IMPLEMENTATION OF PEDAGOGICAL ANALYSIS IN COMBAT – PHYSICAL TRAINING AND ITS FEATURES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
It is necessary that each teacher who conducts a combat – physical training has the skills and skills to be able to analyze the training of his professional counterpart. Properly organized pedagogical control and analysis of the lesson have practically proven the teacher conducting combat – physical and service-related physical training activities to create the basis for the formation and promotion of thinking activities and teaching skills.